Odkrivanje trombofilije v družinah bolnikov z vensko trombozo - Hudournik, Barbara (Medicinski razgledi, 2000)
Inherited trombophilia, state that predisposes individuals to venous thrombosis may be due to deficiency of antithrombin III, deficiency of proteinC or protein S, or resistance to activated protein C. The impact of hereditary trombophilia in familial venous thrombosis is not completely understood. It is known that hereditary trombophilia by itself does not necessarily lead to development of venous thrombosis and that additional risk factors have to be present. In the present study hereditary thrombophilia was investigated in the families of patients with venous thrombosis and hereditarythrombophilia. Differences in biological factors and differences in levels of hemostatic and hematological parameters between subjects with hereditary thrombophilia and venous thrombosis and assimptomatic carriers werestudied. Presence of the risk factor predisposing to venous thrombosis wasalso studied. 14 patients who had been diagnosed with venous thrombosis andinherited thrombophilia (8 females and 6 males, 25-50 years old, with a mean age of 41 years), and 34 close relatives of these patients (15 females and 19 males,11-80 years old, with a mean age of 44 years), were included. In all subjects we measured the activity of antithrombin III, proteins C and S, and resistance to activated protein C, as well as activated partial thromboplastin time, thrombin time, prothrombin time, fibrinogen, lupus anticoagulants, D-dimers, and complete blood cell count. Factors predisposing to venous thrombosis such as immobilisation of a limb, bed rest longer than three days, recent surgery, oral contraception, pregnancy and delivery were also assessed. (Abstract truncated at 2000 characters)
Keywords: krvne bolezni; Thrombophlebitis; trombifilija; Thromboembolism; Diagnosis; genetika; Genetics; Family; Blood coagulation tests; Risk factors; Protein c; Deficiency; Protein s deficiency; Antithrombin iii; diagnostika